Perancangan Struktur Kompensasi Berbasis Nilai Jabatan pada UKM Jasa Pascapanen Agribisnis - Rijki Abi Nugraha; Fakhrul Mubarok; Salsabila Dwi Aryanti; ⁠Febriana Astuti; Micaela Merliana Rolanda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to design a job-based compensation structure for agribusiness post-harvest service SMEs in order to create a more fair and proportional wage system. The study employs a descriptive quantitative approach, with the research subject being SME X, which operates in agricultural product packaging activities in Bogor Regency. Data were collected through observation, semi-structured interviews, and a job analysis questionnaire involving all positions within the organization. Job evaluation was conducted using the point-factor method based on the dimensions of know-how, problem-solving, and accountability, which were translated into ten compensable factors. The results indicate that the highest job value is found in the General Manager position with a score of 319 points, while the lowest value is in the Packing Staff position with a score of 120 points. Job grouping resulted in five job grades reflecting varying levels of responsibility and complexity. Salary mapping analysis identified discrepancies in the actual compensation structure, characterized by limited salary ranges and suboptimal differentiation between grades. The application of the Sequential Dual Scale method produced a wage structure and scale without overlap between grades and increased the total payroll budget by 16.41%. The resulting compensation structure enhances internal equity, improves wage transparency, and supports more systematic human resource management in agribusiness post-harvest service SMEs.